ACHIEVING COCONUT SUPPLY RELIABILITY THROUGH RESEARCH-BASED CROP NUTRITION MANAGEMENT OF COCONUT FARMS IN THE PHILIPPINES - Severino S. Magat, PhD (International Coconut Community Journal, 2003)
A critical review of the PCA’s extensive R & D findings, and field-extension experience, particularly, the Small Coconut Farms Development Project or SCFDP (1990 - 1998) was done. The analysis revealed several key points relevant to pursue a sustained coconut rehabilitation of 750,000 hectares (ha.) @ a 5-year cycle in the wet and intermediate growing zones with judicious fertilization (crop nutrition management). These major points are: (1) at least 2 million (M) ha of current stands of coconut ( more than 95 % local tall varieties) have been suffering from widespread multi-deficiency of plant nutrients such as nitrogen, chloride, sulfur, potassium, phosphorus and micronutrients like boron, zinc and copper; (2) as such, this is a major growth and yield-limiting factor that limits the average annual coconut productivity (40 nuts tree or 1 ton copra/ha); (3) the average performance (1992-95) of the SCFDP farms showed that coconut productivity increased to 91 nuts/tree (from 35 nuts) or to 3.01 tons copra/ha (from only 0.94) after at least 3 years of regular annual application of fertilizers; in 1998 ( post-rehabilitation of 3 years) yields dropped to 70 nuts/tree or 2.21 copra/ha; (4) onwards to year 2010, without management, these SCFDP farms are predicted to further drop to 25.9 nuts/tree ( 0.70 ton copra/ha/yr), based on the estimate 8-9% annual reduction rate of yield; and (5) apparently, nationwide, the SCFDP experience had shown that the soil nutrient-poor coconut farms are only capable of producing only about 1/3 of its achievable yield of 85 – 120 nuts/tree ( 2 –3 tons copra/ha), annually.